Effect of recasting of nickel-chromium alloy on its porosity - Jayant Palaskar; D V Nadgir; Ila Shah (Wolters Kluwer Medknow Publications, 2010)
Statement of Problem: As per the review of literature very few studies have been carried on recasting of dental casting alloy and in particlular its effect on occurrence of porosities. Purpose of Study: This study was designed to find out occurrence of porosities in new alloy and recasted alloy using a scanning electron microscope. Materials and Methods: Different percentage combinations of new and once casted alloy were used to produce twenty five samples. Castings obtained from new alloy were used as control group. All the samples were scanned under scanning electron mocroscope and photographs were taken from three specific sites for comparison. Results: There is no significant difference in occurrence of porosities in casting obtained by using new alloy and recasted alloy. Conclusion: With in the limitations of the study it is conducted that the prorosities will not be affected by recasting of neckel-chromium alloy. Clinical Implication: Porosities in dental casting alloy can alter physical and mechanical properties of the mental which inturn may lead to failure of crown and bridge, and also cast partial denture prosthesis.